On the subplanes of the Hughes planes of odd square prime order (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2000)
In this paper we give a construction of a family of Baer subplanes of the Hughes plane $H$ of odd square prime order $q^2, q ≥ 5$, which are not isomorphic to its well-known desarguesian Baer subplane $H_0 [1, 5.4]$.